Food safety knowledge, sources thereof and self-reported behaviour among university students in Sweden. (July 2020) - Marklinder, Ingela; Ahlgren, Roger; Blücher, Anna; Ehn Börjesson, Stina-Mina; Hellkvist, Frida; Moazzami, Madeleine; Schelin, Jenny; Zetterström, Elin; Eskhult, Gustaf; Danielsson-Tham, Marie-Louise
Abstract: International studies have noted shortcomings in food safety knowledge and behaviour among university students. In general students do not constitute a pronounced risk group but there are wider implications. In a foreseeable future some of them will become pregnant and a majority will be responsible for vulnerable groups in their near environment. A crucial question exists, therefore, about their food safety knowledge and safe food handling practices. The aim of this study is to investigate food safety knowledge, sources thereof and self-reported food safety behavior among university students in Sweden. A quantitative study design using a web-based questionnaire was chosen as the data collection method. The questionnaire was distributed through social media and e-mail. Among the 606 respondents from 24 Swedish universities 80% were 18-30 years and 78% were women. The average number of correct answers on the knowledge questions was 7.61 out of 12 (63.4%). The foremost source of food safety knowledge was "Family and friends" (45%). Just 21.1% reported Food safety education as a source, although 35.6% had experience of a course in food hygiene/safety and/or microbiology. Respondents who reported "Family and friends" to be the foremost food safety source of knowledge also got a significantly lower rate of correct answers. Students who estimated their food safety knowledge to be good also had more correct answers. Experience of food safety education at secondary school/university/working place/polytechnic school significantly correlated with more correct answers on the knowledge questions and indicated a safer self-reported behaviour. Those with fewer correct answers also reported more unfavourable behaviours. The present study indicates that education promotes more optimal behaviors. The authors would suggest a more systematic food safety education at younger ages. Highlights: Food safety study targeting university students from 24 Swedish universities Experience of food safety education significantly showed more knowledge Experience of food safety education indicated more optimal behavior The foremost sources of food safety knowledge were family and friends The project is conceptualized and performed by a National food safety network